Using Photography to Enhance Development of Self, Professional Identity, and Multicultural Awareness. Issue 1 (2nd January 2019) - Schmidt, Maya K.; Murdock Bishop, Jennifer L.; Becker, Kent
ABSTRACT: Counseling can be a vulnerable process for clients and counselors alike. Counselors-in-training often find their early development to be an ambiguous and anxiety-provoking process. Both metaphors and experiential activities are effective methods in counselor training for addressing the ambiguity of counseling and the concerns experienced by counseling students. This article describes how counselor educators can use photography as a metaphor to support counselor development. We also outline four creative photography activities designed to foster self-reflection, professional identity development, and multicultural awareness among counselors-in-training.